2016
DOI: 10.3892/mmr.2016.5721
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture of fibroblast-like synoviocytes with umbilical cord-mesenchymal stem cells inhibits expression of pro-inflammatory proteins, induces apoptosis and promotes chondrogenesis

Abstract: The present study aimed to investigate the effect of co‑culture of fibroblast‑like synoviocytes (FLS) with human umbilical cord‑mesenchymal stem cells (UC‑MSCs) on rheumatoid arthritis (RA) and to understand the mechanisms that mediate the induced changes. FLS and UC‑MSCs were isolated and cultured individually, FLS were then cultured with or without UC‑MSCs. The phenotype of UC‑MSCs was analyzed prior to co‑culture. The UC‑MSCs were successfully isolated and expanded, and exhibited a fibroblast‑like morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…They also suppress T cell activations and induced the generation of Tregs . A coculture of FLS with UCB‐MSCs inhibited the expression of pro‐inflammatory cytokines and chemokines IL‐1β, IL‐6, and the chemokine (C‐C motif) ligand‐2; it further induced FLS apoptosis and promoted chondrogenesis . hUCB‐MSCs downregulate the secretion of TNF‐α from activated macrophages and also accelerated anti‐inflammatory M2 polarizations in a paracrine manner .…”
Section: Discussionmentioning
confidence: 99%
“…They also suppress T cell activations and induced the generation of Tregs . A coculture of FLS with UCB‐MSCs inhibited the expression of pro‐inflammatory cytokines and chemokines IL‐1β, IL‐6, and the chemokine (C‐C motif) ligand‐2; it further induced FLS apoptosis and promoted chondrogenesis . hUCB‐MSCs downregulate the secretion of TNF‐α from activated macrophages and also accelerated anti‐inflammatory M2 polarizations in a paracrine manner .…”
Section: Discussionmentioning
confidence: 99%
“…hMSCs have strong anti‐inflammatory and immunomodulatory properties; the extent to which hMSCs sense and respond to immune derangement and restore immune homeostasis is a matter of controversy ( 19 ). Studies show that treatment with hMSCs reduces the inflammatory response of peripheral blood mononuclear cells from patients with RA ex vivo ( 20 ). The ultimate goal of the studies described is to validate a potency assay for cellular products (hMSCs delivered by local injection or systemic infusion, or hMSC CM or exosomes delivered similarly) to be used therapeutically in RA and related autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…UC-MSCs have been demonstrated to secrete BMP2 in vitro and to induce the increase of endogenous BMP4, 5, and 7 levels in vivo [ 58 60 ]. In addition, UC-MSCs induce overexpression of GDF5/BMP14/CDMP1, promoting chondrogenic differentiation in cocultures with fibroblast-like synoviocytes, thus, suggesting their potential in cartilage repair [ 61 ]. Moreover, UC-MSCs respond to BMP6 via decapentaplegic homolog (SMAD) signaling (SMAD 1/4/5, BMPR1A, and BMPR2 receptors) enhancing osteogenic differentiation [ 62 ].…”
Section: Regeneration Mechanisms Of Uc-mscs For Cartilage Diseasesmentioning
confidence: 99%
“…Interestingly, UC-MSCs displayed superior anti-inflammatory, immunomodulatory, and trophic effects compared to adult MSCs including articular cartilage (AC), Hoffa's fat pad (HFP), synovial membrane (SM), and maintain their immunomodulatory and anti-inflammatory properties after differentiation [ 50 , 84 , 95 ]. Moreover, coculture experiments of UC-MSCs and articular cartilage cells (ACs), fibroblast-like synoviocytes (FLSs), and nucleus pulposus cells (NPCs) showed their suitability for the treatment of arthritis, synovitis, and IVD degeneration [ 61 , 96 98 ]. Finally, there are several cartilage tissue engineering studies that demonstrated the osteochondral differentiation capacity of UC-MSCs in different scaffold constituted by acellular cartilage extracellular matrix (ACECM), alginate enriched in hyaluronic acid (Alg/HA), polycaprolactone/collagen (PCL/Coll), polyglycolic acid (PGA), poly L-lactide/D-lactide/glycolide (PLGA), poly-L-lactic acid (PLLA), polyvinyl alcohol-polycaprolactone (PVA-PCL), and silk fibroin/hyaluronic acid (SF/HA).…”
Section: Preclinical and Clinical Studies Of Uc-mscs For The Treatment Of Cartilaginous Diseasesmentioning
confidence: 99%